For positivist organization theory : proving the hard core - Donaldson, Lex (Sage Publications, 1996)
Organization theory is presently dominated by theories of strategic choice and politics. Managers are seen as exercising a wide choice and maximizing their personal self-interest through complex power struggles. This stimulating volume challenges these views, arguing instead that managerial decisions are determined by the situation and serve the interests of the whole organization. Showing that organizations follow laws which generalize across organizations of many different kinds in many different national cultures, the book rejects the model of organizational configurations or types. The aut.